Rivaroxaban solid dispersions for dissolution enhancement and formulation of mouth disintegrating tablets - Priyadarshan, Kalki Ranjan; Sahu, Asish; Mahapatra, Anjan Kumar; Chowdary, K. A; Nahak, Ajit; Patra, Ruchita Kumari (Journal of Applied Pharmaceutical Research, 2024)
Background: Work is carried out to improve rivaroxaban's dissolution rate (DR) and develop mouth-disintegrating tablets for rapid onset of action. Objectives: The work objective was to improve the dissolution rate of rivaroxaban using PEG 6000 by preparing its solid dispersions (SDs) further to prepare mouth-disintegrating tablets (MDTs). Methods: Methods like physical mixing, melting, and solvent evaporation were used to prepare SDs at 1:0.5, 1:1, and 1:1.5 w/w ratios of rivaroxaban with PEG 6000 were prepared. Differential scanning calorimetry (DSC) and Infrared spectroscopy (IR) were used to characterize the SDs. The selected solid dispersion at an appropriate drug: carrier ratio was used to develop MDTs by direct compression, using super disintegrants. Results: The SDs show improved solubility and rate of dissolution. SDs developed using a melting or solvent evaporation technique showed a more than two-fold increase in dissolution rate. In the dissolution study, after 60 min, the pure drug dissolved 45 %, while the prepared SDs showed almost more than 90 % within the same period. No significant drug carrier interaction was observed in the IR and DSC studies. However, minor shifts in peak values were observed for the characterization of functional groups in the drug structure. Conclusions: Formulation of solid dispersions of the drug with PEG 6000 is a successful approach for the dissolution rate improvement of rivaroxaban. This work for dissolution rate improvement of rivaroxaban using PEG 6000 showed significant improvement in dissolution rate at a 1:1 w/w ratio prepared by solvent evaporation method, which was further selected for mouth disintegrating tablet formulation.